Determinants of the Implied Volatility Function : Empirical Evidence from the Euro Stoxx 50 Option Market - Tuominen, Matias (My University, 2026)
This thesis investigates the determinants of the implied volatility function (IVF) within the Euro Stoxx 50 index option market. While the Black-Scholes model remains an industry standard for option pricing, empirical evidence consistently highlights its failure to account for the variance of implied volatility across different strike prices, a phenomenon known as the volatility smile or smirk. The objective of this study is to examine how market momentum, historical volatility, and trading volumes affect the daily variations in the IVF. The empirical analysis was conducted using a two-stage framework with daily data spanning from January 2016 to December 2025, strictly limited to options with a constant 30-day maturity. In the first stage, the daily IVF was modeled using a quadratic polynomial to extract the specific coefficients for its level, slope, and curvature. In the second stage, the variations in these coefficients were analyzed against the explanatory variables using time-series OLS regressions with Newey-West robust standard errors. The empirical findings demonstrate that downward market momentum and historical volatility are the most significant drivers of the IVF. Both variables exhibit a strong positive correlation with the overall level of the IVF, and a significant negative correlation with its slope and curvature. Economically, these results provide robust evidence for asymmetric hedging demands and the "crash-phobia" phenomenon. As market uncertainty or downward momentum increases, investors disproportionately bid up the prices of out-of-the-money (OTM) put options to insure their portfolios against sudden downturns, effectively steepening the downward slope of the smirk. The thesis confirms that macroeconomic variables systematically shape option pricing and market dynamics.

Tämä tutkielma tarkastelee implisiittisen volatiliteettifunktion (IVF) selittäviä muuttujia Euro Stoxx 50 -indeksin optiomarkkinoilla. Vaikka Black-Scholes-malli on edelleen optioiden hinnoittelun yleinen standardi, empiirinen näyttö korostaa toistuvasti sen kykenemättömyyttä selittää implisiittisen volatiliteetin vaihtelua eri toteutushinnoilla, mikä on ilmiö, joka tunnetaan volatiliteettihymynä tai -vinoumana. Tämän tutkimuksen tavoitteena on tarkastella, kuinka markkinamomentum, historiallinen volatiliteetti ja kaupankäyntivolyymit vaikuttavat IVF:n päivittäisiin vaihteluihin. Empiirinen analyysi toteutettiin kaksivaiheisella menetelmällä käyttäen päivittäistä dataa tammikuusta 2016 joulukuuhun 2025, rajaten tarkastelun tiukasti optioihin, joilla on 30:n päivän maturiteetti. Ensimmäisessä vaiheessa päivittäinen IVF mallinnettiin toisen asteen polynomilla sen tason, kaltevuuden ja kaarevuuden kertoimien eristämiseksi. Toisessa vaiheessa näiden kertoimien vaihteluita analysoitiin suhteessa selittäviin muuttujiin käyttämällä aikasarjojen OLS-regressioita ja Newey-Westin robusteja keskivirheitä. Empiiriset tulokset osoittavat, että negatiivinen markkinamomentum ja historiallinen volatiliteetti ovat IVF:n merkittävimmät ajurit. Molemmat muuttujat korreloivat voimakkaan positiivisesti IVF:n yleisen tason kanssa sekä merkittävän negatiivisesti sen kaltevuuden ja kaarevuuden kanssa. Taloudellisesti nämä tulokset tarjoavat vankkaa näyttöä epäsymmetrisestä suojautumiskysynnästä ja niin sanotusta romahduspelko-ilmiöstä (crash-phobia). Markkinoiden epävarmuuden tai negatiivisen momentumin kasvaessa sijoittajat nostavat suhteettomasti out-of-the-money (OTM) -myyntioptioiden hintoja suojatakseen salkkujaan äkillisiltä kurssilaskuilta, mikä käytännössä jyrkentää vinouman alaspäin laskevaa kaltevuutta. Tutkielma vahvistaa, että makrotaloudelliset muuttujat muokkaavat järjestelmällisesti optioiden hinnoittelua ja markkinadynamiikkaa.
Keywords: Implied volatility function; Implied volatility surface; Black-Scholes model; Implisiittinen volatiliteettifunktio; Implisiittinen volatiliteettipinta; Black-Scholes-malli